Estimation of Concentration Levels For Both IL-23 and IL-1β in Multiple Sclerosis Patients - Mohammed Abd-Alameer , Ali (Hammurabi Journal of Medical Sciences, 2025)
Background: Multiple sclerosis (MS) is an inflammatory condition that affects the central nervous system, leading to dysfunction of neural function. Clinically shown with different temporal and pathological patterns and is distinguished by immunity cells. Invasion of the nervous system, removal of the myelin cortex, nerve axis damage, and relapse. Many of the cytokines that played an important role in the pathogenesis of MS were interleukin-1 beta and interleukin-23. Objectives: This study aims to assess the concentration levels of interleukin-1 beta and interleukin-23 by measuring them in the serum of MS patients, studying the effect of these variants in the disease, predicting their development, and determining the degree to which these cytokines influence one another. Materials and methods: Samples of 50 MS patients were collected after being diagnosed by doctors and 50 healthy people as a control group at Imam Sadiq Hospital in Babylon Governorate between September and December 2024, and the enzyme-related immunoabsorption (ELISA) method was used to measure the concentration level of cytokines in all patients' serum and the control group. To explore their potential role in MS pathogenesis. Results: showed that the concentration levels of the interleukin-1 beta and interleukin-23 in MS were higher at the probability level (P <0.05), while the levels of these cytokines decreased in the control group. Conclusion: According to the results of the current study, MS patients have a higher concentration level for both interleukin-1 beta and interleukin-23 in their serum compared to the control group.